Interaksi Sosial Termediasi Pembaca Alternative Universe (AU) “Slowmotion” : (Studi Netnografi dalam Kanal Close and Private Mediated Interaction Grup Telegram “Pasukan Bawah Tanah”) - Afrilia, Roesdiana; Hidayat, Medhy Aginta (Prodi Sosiologi Universitas Mataram, 2024)
This article aims to explain the phenomenon of mediated social interaction of Alternative Universe (AU) story readers through Telegram social media which has characteristics as a close and private group, and to find out how AU readers form and maintain online social networks on Telegram. The method used in this research is a qualitative method using a netnography approach. In data collection techniques, researchers used observation, in-depth interviews, and documentation. To determine the informants in this study, researchers used purposive sampling technique, by determining in advance the criteria for informants to be studied. The data validity check technique in this research uses source triangulation technique. The results of this study show that even though they do not know each other personally, the AU story readers who are members of the “'Pasukan Bawah Tanah” Telegram group have intense mediated social interactions, by following every project made by the AU writer “Slowmotion” and establishing close friendships between members. In addition, the information distribution process carried out by AU readers who are members of the “'Pasukan Bawah Tanah” Telegram group is able to produce a number of joint content collaborations through the exchange of ideas between writers and group members. In these ways, the readers of the AU story “Slowmotion” and the members of the “Underground Troops” group can maintain the existence of themselves and their groups in the mediated social network through Telegram.